Literature and Contemporary Ideological Issues (مجلة الواحات للبحوث والدراسات, 2025)
Literature's textual compositions (linguistics and semantics) extend beyond the poetics that structuralist criticism has primarily explored. Rather, ideological frameworks shape it as a creative product, influencing both its explicit and implicit meanings. Therefore, this study aims to explore the relationship between literature and ideology, revealing that a literary work can encompass various human experiences and ideological orientations. As such, literature cannot be seen as an entirely individual creative practice nor a purely ideological process. Instead, it is the reconfiguration of the creator's experience and ideology in a new form, which we call the literary work. Consequently, the literary work is a reproduction of ideology, not its creation. Literature is a manifestation of ideology and one of its fields.Keywords: Ideology, Literature, Issues, Thought, Contemporary Ideology